2021
DOI: 10.1177/08971900211015055
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Anticoagulation on COVID-19 (SARS CoV-2) Patient Outcomes: A Systematic Review

Abstract: Background: Emerging data suggest that coagulopathy, cytokine storm, and acute respiratory distress syndrome are associated with the 2019 coronavirus disease (COVID-19). The prevalence of hypercoagulable state in these patients is unknown, but appears to be higher compared to those with other critically ill patients. Elevated D-dimer, large blood vessels clots, deep vein thrombosis, pulmonary embolism and disseminated intravascular coagulation have been reported in patients diagnosed with COVID-19 either on ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…23 A systematic review of 4 studies evaluating the impact of anticoagulation on COVID-19 patient outcomes found decreased mortality in these patients with the use of therapeutic doses of anticoagulation. 24 However, the risk of increased bleeding due to anticoagulation must be weighed against the benefits. Oral anticoagulants carry a 13.4% case fatality rate for major bleeds.…”
mentioning
confidence: 99%
“…23 A systematic review of 4 studies evaluating the impact of anticoagulation on COVID-19 patient outcomes found decreased mortality in these patients with the use of therapeutic doses of anticoagulation. 24 However, the risk of increased bleeding due to anticoagulation must be weighed against the benefits. Oral anticoagulants carry a 13.4% case fatality rate for major bleeds.…”
mentioning
confidence: 99%
“…Multiple systematic reviews and meta-analyses reported variable VTE incidence in patients with COVID-19 according to the diagnostic approach, whether passive upon presentation of clinical manifestation (9.5%) or active search (14.1%), 26 and critical clinical condition, regardless of the patient being in intensive care (13.7%) or on ward beds (3.5%). 1 , 2 , 4 , 12 , 18 , 19 , 20 , 21 When in intensive care and under an active diagnostic search protocol, the incidence of VTE can increase up to 4 times, with a prevalence of 48% (95% Confidence Interval, 95% CI: 0.33 to 0.63). 2 There is even a discussion about whether patients with COVID-19 develop more thrombosis compared to non-COVID-19 patients with the same severity.…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 pandemic, however, the application of this knowledge became difficult for those involved in direct patient care due to the multiplicity and variation in the recommendations for thromboprophylaxis, 17 , 18 as well as the low or very low quality of the studies that such recommendations were based on. 19 , 20 One reason may be due to the COVID-19 infection itself and its severe disease pathogenesis, which was then (and still is) in the discovery phase. In addition, the risk stratification approaches used among the patients studied and the anticoagulation strategies, with their recommended drugs and dosages, showed significant heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of 64 studies associated an improvement in pulmonary oxygenation, decreased coagulopathy markers, and decreased mortality in COVID-19 patients with prophylaxis and high dose anticoagulation. [45] Another study showed a significant decrease in mortality in COVID-19 patients receiving anticoagulation. Prophylactic anticoagulation had an RR of mortality of 0.54, and therapeutic anticoagulation showed a relative risk of mortality of 0.4.…”
Section: Discussionmentioning
confidence: 99%